Effect of Phenobarbitone Treatment Against Signal Grass (Brachiaria decumbens) Toxicity in Sheep - Ab. Hamid, Hasiah; H. A., ElSheikh; Abdullah, Abdul Salam; Hussain, Mohd Khairi; Rajion, Mohamed Ali (Elsevier Science, 2000)
The effect of phenobarbitone against signal grass (Brachiaria decumbens) toxicity was studied in 26 male crossbred sheep. Grazing on signal grass significantly decreased the concentration of cytochrome P-450 and the activity of drug metabolizing enzymes, viz. aminopyrine-N-demethylase, aniline-4-hydroxylase, UDP- glucuronyltransferase and glutathione-S-transferase in liver and kidneys of affected sheep.